The Flat-Rate Pricing Paradox: Conflicting Effects of “All-You-Can-Eat” Buffet Pricing - Just, David R; Wansink, Brian (The Review of Economics and Statistics, 2011)
Are price and consumption independent in flat-rate price service contexts? A field experiment at an all-you-can-eat pizza restaurant shows that a 50% discount on the price of the meal led customers to consume 27.9% less pizza (2.95 versus 4.09 pieces). A second analysis indicated that individual taste ratings of this pizza tended to be inversely related to how much is consumed. One possible interpretation of these two findings is that individuals in a flat-rate (or fixed-price) context may consume the amount that enables them to get their money's worth rather than consuming until their marginal utility of consumption is 0.